Ethical leadership, organizational citizenship behaviour and work life balance among government secondary school teachers in Malaysia - Kay, Ee Tong; Neow, Choo Kean; Ooi, Mun Yee; Yang, Zhi Xin (2023)
Nowadays, educational industry is crucial in facilitating an individuals’ growth. Various industries have been affected during the COVID-19 Pandemic and also post COVID-19 pandemic, and of course, secondary schools are inevitable. Secondary school teachers working mode has been influence and these changes require teachers to adopt and cope with the new teaching or working mode quickly to deal with students and school management. Nonetheless, these changes will indirectly affect the teachers work life balance and extra-role behaviours. Hence, this research intends to test the impact of the independent variables on extra-role behaviours in the context of Covid-19 pandemic. A total of 437 respondents’ data is collected and used in this study. The data are collected from multiple secondary schools in Selangor, Malaysia. Multiple Linear Regression Analysis are used to examine the impact of independent variables on dependent variables (OCB). Statistical Package for the Social Sciences version 26 (SPSS v26) was used to run the reliability analysis and test of hypothesized relationships of this research. The conclusion of the study has found that the two independent variables (ethical leadership, work life balance) have positive influencing with organizational citizenship behaviour (OCB). The managerial implication, limitation and recommendation are discussed at the end of the research.